Informe Hidrometeorológico de la cuenca del Río Colorado [marzo 2023] - Aumassanne, Carolina Manuela; Oricchio, Patricio; Fontanella, Dardo Roy; Beget, Maria Eugenia; Gattinoni, Natalia Noemí; Masseroni, Maria Lujan; Varela, Ayelén Celeste; Ramis, Vanesa; Espindola, Aime; Dunel Guerra, Luciana Gisele; Vanzolini, Juan Ignacio; Storniolo, Romina; et al. (Agencia de Extensión Rural 25 de Mayo, INTA, 2023)
AER Colonia 25 de Mayo